RISK FACTORS OF URINARY BLADDER CANCER IN PESHAWAR REGION OF KHYBER PUKHTOONKHAWA - Ahmad, Muhammad Riaz; Pervaiz, Muhammad Khalid (Journal of Ayub Medical College Abbottabad, 2010)
Background: Urinary Bladder cancer is a fatal disease. No work about its risk factors has been conducted in northern Pakistan. This case control study was conducted in order to investigate the risk factors of the urinary bladder cancer in that area. Method: For this study 150 subjects including 50 cases and 100 controls were interviewed from the 2 tertiary care hospitals of Peshawar and the information was collected about the characteristics like gender, age, smoking habits, family history of cancer, etc. Descriptive and inferential statistics were used to explain the risk factors of the disease. Odds ratios and 95% Confidence Intervals were computed by using logistic regression model. Results: The odds ratio and 95% confidence interval for chemical exposure are 4.637 and (1.022-21.053), for cigarette smoking 19.526 and (4.688- 81.329), for lifestyle 0.171 and (0.031-0.943), for fluid consumption 0.025 and (0.005-0.115), for fried items 5.934 and (1.429-24.648), and for fruits are 0.173 (0.045-0.660), respectively. Conclusions: Chemical exposure, cigarette smoking, and high use of fried items increase the risk of urinary bladder cancer. Moderate lifestyle, high fluid consumption and use of fruits are protective against the disease. Keywords: Bladder cancer, Controls, Odds ratio, Questionnaire, Risk factors